2015
DOI: 10.1002/mus.24574
|View full text |Cite
|
Sign up to set email alerts
|

Radial nerve measurements in nonsymptomatic upper extremities of Filipinos: A cross‐sectional study

Abstract: RN reference values can now be used for comparison in elbows with LE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…8,[33][34][35] Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides. 20,[34][35][36][37][38][39][40][41][42][43][44][45][46] The greatest variability in nerve CSA was seen in the brachial plexus, tibial-popliteal fossa, and all three sciatic nerve small groups. When combining all anatomical locations for individual nerve measurements, the tibial nerve (n = 2916 nerves) was the most assessed, followed by the common fibular nerve (n = 2580 nerves), radial nerve (n = 2326 nerves), sciatic nerve (n = 1470 nerves), sural nerve (n = 1316 nerves), and brachial plexus (n = 1314 nerves).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[33][34][35] Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides. 20,[34][35][36][37][38][39][40][41][42][43][44][45][46] The greatest variability in nerve CSA was seen in the brachial plexus, tibial-popliteal fossa, and all three sciatic nerve small groups. When combining all anatomical locations for individual nerve measurements, the tibial nerve (n = 2916 nerves) was the most assessed, followed by the common fibular nerve (n = 2580 nerves), radial nerve (n = 2326 nerves), sciatic nerve (n = 1470 nerves), sural nerve (n = 1316 nerves), and brachial plexus (n = 1314 nerves).…”
Section: Resultsmentioning
confidence: 99%
“…Five groups (axillary, femoral, long thoracic, saphenous, and suprascapular–supraspinatus fossa) were comprised of just one study 8,33–35 . Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides 20,34–46 . The greatest variability in nerve CSA was seen in the brachial plexus, tibial–popliteal fossa, and all three sciatic nerve small groups.…”
Section: Resultsmentioning
confidence: 99%
“…In studies involving Asian patients, these have been limited to one ethnic group within that population. [ 9 10 11 12 13 14 15 16 ] In one study, the authors investigated the differences in median nerve (MN) CSA between Dutch and Indian participants,[ 17 ] suggesting that ethnicity has a significant impact on nerve CSA. Malaysia has a multiethnic population comprising three major ethnic groups (Malay, Chinese, and Indian).…”
Section: Introductionmentioning
confidence: 99%